Electronic Participation 7th IFIP 8.5 International Conference, ePart 2015, Thessaloniki, Greece, August 30 -- September 2, 2015, Proceedings - Tambouris, Efthimios; Panagiotopoulos, Panos; Sæbø, Øystein; Tarabanis, Konstantinos; Wimmer, Maria A.; Milano, Michela; Pardo, Theresa (Information Systems and Applications, incl. Internet/Web, and HCI, 2015)
This book constitutes the refereed proceedings of the 7th IFIP WG 8.5 International Conference on Electronic Participation, ePart 2015, held in Thessaloniki, Greece, in August/September 2015. The 12 revised full papers presented were carefully reviewed and selected from 19 submissions. The papers have been organized in the following topical sections: eParticipation and social media, delibration and consultation, evaluation, and policy formulation and modelling.